Influencing Factors on the Pre-ageing Preparedness among People Living in Nongplalai Subdistrict, Mueang District, Saraburi Province - แข็งกสิกรณ์, กัญญารัตน์; สุธีประเสริฐ, ธานินทร์; เอี่ยมระหงษ์, วิโรจน์; เนตรศรีทอง, สุวรรณี; บุญศิริลักษณ์, สุภาพร (Journal of Health Science of Thailand, 2022)
This cross-sectional descriptive research aimed to examine factors affecting self-preparedness before reaching seniority age among people living in Nongplalai Subdistrict, Mueang District, Saraburi Province. The participants were 351 people aged 50 - 59 years old recruted by cluster sampling. A set of questionnaire was employed as data collecting tool with reliability at 0.878; and the data were analyzed by using descriptive statistics including frequency, percentage, mean, standard deviation, maximum, minimum, t-test and one-way ANOVA. The results showed that approximately two-thirds of participants were female with the average age of 54.38 years old. Most people were married and had children. Half of them graduated from primary school with no part-time job. Employment income was used for their on-cost expenses, without saving. Approximately one in five participants had low-income family with debt burdens. Most participants were living in their own houses with the average family member of 3.68 people. In terms of health, around four in five of participants had no underlying disease and more than half of of them used health services under universal coverage scheme. Five aspects for self-preparedness before ageing included economic, household, physical health, mental health, and time management which were rated at a moderate level. (mean=3.39, 3.22, 3.41, 3.57, 3.55 and 3.17, respectively) However, there were significantly differences across educational level, marital status, career, family income, household, and health insurance type (p<0.05). This research suggested setting projects for people in the community including supporting career development, encouraging health promotion club in physical and interactive activities.